The Colorado Learning Attitudes about Science Survey (CLASS): The Study of Validity and Reliability - Adem BAYAR; Orhan KARAMUSTAFAOĞLU (International Journal of Assessment Tools in Education)
The aim of this research is to adapt the Colorado Learning Attitudes about Science Survey (Adams et al., 2006) to Turkish and to examine its psychometric properties. The research was conducted on 400 9th grade students from the Directorate of Educational Department in Amasya, Turkey. The results of exploratory and confirmatory factor analyses clearly showed that this scale yielded 8 factors, as original form and that the model was well fit. Internal consistency coefficients varied between .72-.84 and test-retest reliability coefficients varied between .85-.93. Corrected item-total correlations ranged .51 to .75, and according to t-test results differences between each item’s means of upper 27% and lower 27% points were significant. As a result, Colorado Learning Attitudes about Science Survey can be used as a valid and reliable instrument in education.